1991
DOI: 10.1161/01.res.68.4.1045
|View full text |Cite
|
Sign up to set email alerts
|

Fasting in vivo delays myocardial cell damage after brief periods of ischemia in the isolated working rat heart.

Abstract: To assess the effects of fasting on recovery of function and exogenous glucose metabolism after 15 minutes of total ischemia, we perfused isolated working rat hearts from fed and fasted animals. Hearts were perfused in a recirculating system with bicarbonate buffer containing glucose (10 mM). Mechanical performance, release of marker proteins for ischemic membrane damage (lactate dehydrogenase, myoglobin, citrate synthase), and the concentrations of lactate and glucose in the perfusion medium were measured ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
35
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 31 publications
8
35
0
Order By: Relevance
“…Previous studies have already suggested that, in normal rats, fasting overnight improves cardiac performance (23,24). Consistent with these reports, we have found that fasting in lean Zucker rats increases cardiac output.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have already suggested that, in normal rats, fasting overnight improves cardiac performance (23,24). Consistent with these reports, we have found that fasting in lean Zucker rats increases cardiac output.…”
Section: Discussionsupporting
confidence: 92%
“…It has been confirmed as previously reported the protective effect of fasting on the myocardial performance in ischemic-RP hearts (10, 12,17,18,26). In addition, since the preischemic glycogen stores were higher in hearts from control fasted rats and glycogen depletion reached similar values after sustained ischemia in the fed and fasted groups, it seems evident that the amount of glycogen broken down was greater in the fasted hearts.…”
Section: Discussionsupporting
confidence: 88%
“…This finding contrast with previously reported data (17,18) but agree with another papers which showed that creatine kinase leakage as well as infarct size were similar in the fed and fasted groups (10, 26,32). From present data ir arises that the alleviation of the ischemic dysfunction in the fasted rat heart ought to be an effect exerted only on the viable myocardium.…”
Section: Discussionsupporting
confidence: 57%
“…79 Many other studies, however, have shown that protection of the heart against ischemic injury is related to glycogen availability. 73,81,[105][106][107][108][109] The absolute amount of glucose moieties arising from glycogen is not negligible at the onset of ischemia. In isolated perfused hearts subjected to low-flow ischemia, glycogen breakdown provides, during the first 15 minutes, about 60 mol glucose equivalents per gram dry weight, whereas during the same period, glucose uptake offers about 35 mol glucose per gram.…”
Section: Glycogen Metabolismmentioning
confidence: 99%